2005
DOI: 10.1109/tro.2004.838030
|View full text |Cite
|
Sign up to set email alerts
|

How to keep from falling forward: elementary swing leg action for passive dynamic walkers

Abstract: Abstract-Stability control for walking bipeds has been considered a complex task. Even two-dimensional fore-aft stability in dynamic walking appears to be difficult to achieve. In this paper we prove the contrary, starting from the basic belief that in nature stability control must be the sum of a number of very simple rules. We study the global stability of the simplest walking model by determining the basin of attraction of the Poincaré map of this model. This shows that the walker, although stable, can only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
90
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(97 citation statements)
references
References 19 publications
3
90
0
Order By: Relevance
“…In a previous study we showed that there is indeed such a trade-off between energy consumption and robustness (Verdaasdonk et al 2007a) in a similar CPG-controlled bipedal walking model (although that one could not passively walk down a slope, because it had human inertial distribution). The study showed that the robustness against large perturbations is increased with the velocity of the swing leg, which agrees with the statement of Wisse et al (2005) that you will never fall forward if the swing leg is put fast enough in front of the stance leg. There are two methods to increase swing leg velocities and by that the robustness against large perturbations.…”
Section: Robustness Versus Efficiencysupporting
confidence: 86%
“…In a previous study we showed that there is indeed such a trade-off between energy consumption and robustness (Verdaasdonk et al 2007a) in a similar CPG-controlled bipedal walking model (although that one could not passively walk down a slope, because it had human inertial distribution). The study showed that the robustness against large perturbations is increased with the velocity of the swing leg, which agrees with the statement of Wisse et al (2005) that you will never fall forward if the swing leg is put fast enough in front of the stance leg. There are two methods to increase swing leg velocities and by that the robustness against large perturbations.…”
Section: Robustness Versus Efficiencysupporting
confidence: 86%
“…However, this is not a necessary measure [1]. The idea of adjusting the step frequency by a hip spring was also applied to prevent stumbling by shortening the swing phase of planar passive dynamic walking robots with trunk in simulation [41] and experiment [40].…”
Section: Introductionmentioning
confidence: 99%
“…It has high compliance and can provide large force with a lightweight mechanism. Wisse, et al built several biped robots with McKibben muscle actuators to walk on a flat floor, namely, Mike [11,12], Max [13], and Denise [14]. Hosoda and his research group also developed a series of pneumatic actuated biped robots [15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%